Exploring biological classification: The unique organism project. (2nd October 2017) - Haines, Sarah; Richman, Laila; Hartley, Renee; Schmid, Rachel
ABSTRACT: The unique organism project was designed as a culminating assessment for a biological classification unit in a middle school setting. Students developed a model to represent their unique organism. Using the model, students were required to demonstrate how their unique organism interacts with its environment, and how its internal and external structure and organization allowed it to carry out those interactions. The NGSS Cross Cutting Concepts of structure and function, systems, and system models along with the Science & Engineering Practice of constructing models were integrated and emphasized throughout the unit.